A case of chronic suppurative osteomyelitis of the mandible in a child - ARIKAWA, Kazuhiro; DOHGOMORI, Hiroshi; SUGIHARA, Kazumasa; KAWASHIMA, Kiyomi; YOSHIDA, Masashi; KUBO, Hiroaki; NITTA, Tetuya; SHOMURA, Kenji; YAMAGUTI, Kojiro; MUKAI, Hiroshi; KAMIKAWA, Yoshiaki; ISHIGAMI, Teturo (Pediatric Oral and Maxillofacial Surgery, 1998)
Chronic suppurative osteomyelitis of the mandible is very rare in infants and small children. We encountered a 5-year-old boy with chronic suppurative osteomyelitis of the mandible who showed extensive mandibular destruction from the right mandibular deciduous molar region to the mandibular ramus. Orthopantomogram revealed a motheaten appearance. Osteomyelitis of the mandible which progresses causing extensive mandible destruction, is considered to affect mandibular development, and it may result in sequelae including esthetic impairment such as facial deformity and impairment of the masticatory function. However, bone remodeling is remarkable in infants and small children, and early bone regeneration can be expected. We attempted hyperbaric oxygen therapy (HBO) to promote early bone formation and minimize esthetic and functional impairment with satisfactory results. Cooperation of parents is necessary for HBO therapy for small children. It might be troublesome that the patient and parents are obliged to the stay in the HBO room during the treatment. However, our patient showed early bone regeneration. Therefore, HBO is considered to be an adjunctive treatment positively acceptable to promote bone formation for the treatment of infants and small children with bone destructive changes.